IMPULSE BUYING BETWEEN DIGITAL MARKETING AND STORE ATMOSPHERE - Sumarga, Hendi Eka; Rofiq, Iwan Setiawan; Munandar, Raji (Universitas Muhammadiyah Tangerang, 2025)
This study aims to analyze the relationship between Digial marketing, Store Atmophere and Impulse buying, a case study of super indo teras kota. This study uses quantitative methods and survey research by distributing questionnaires to urban super consumers. Samples were taken from 96 respondents using the purposive sampling technique. The analysis methods used are Descriptive Statistical Analysis, Validity Test, Reliability Test, Simple Linear Regression, Multiple Linear Regression, Simple Correlation, Determination Coefficient, t-test, and f-test with the help of IBM SPSS V.26 Software. The results showed that the Digital Marketing Style (X1) variable, Store Atmophere (X2), simultaneously had a positive and significant influence on Impulse Buying Performance (Y) with Fcal greater than Ftable (279,305>3,094) with a significance value of 0.00 < 0.05.